Response of The Ionospheric E- Region Critical Frequency and Virtual Height to the Solar Cycle 22 over Baghdad - Al-Shakarchi, Duraid A.; Abd-Almajied , Mohammed I (Iraqi Journal of Science, 2022)
The aim of this study is to investigate the response of the Ionospheric E- region critical frequency foE and virtual height h’E parameters to the solar cycle 22 over Baghdad city (latitude 33.3˚N, longitude 44.4˚E). Both parameters display a high relationship with the sunspot relative number within the ascending and descending phases of the solar cycle. The E - region response to the solar activity is obvious around noon, sunrise and sunset times. Moreover, the gap between local mid-afternoon, dawn and sunset values expands as solar activity rises. In the declining phase, there is an aspect that results in a peak of disturbance. This portion may have linked to coronal holes and resulted in high disturbance peak during 1992-1994. The impact of this portion is obvious in raising the values of foE, especially in 1993.